Ketepatwaktuan Publikasi Laporan Keuangan Selama Masa Pandemi Covid-19: Faktor Audit Tenure, Reputasi KAP, dan Financial Distress - Ela Annisa; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This research was conducted to determine the influence of auditee tenure, reputation KAP, financial distress to companies listed on the Stock Exchange Indonesia for the 2019-2020 period in which economic conditions were hit by the covid-19 pandemic. The population of this research is late companies publication of financial reports as many as 66 populations with a sampling technique using purposive sampling method of 31 samples company. The results of the research processed using the logistic regression method show that the auditee tenure, reputation KAP, and financial distress has no effect on the timeliness of report publication finances that occurred during the covid-19 pandemic.